Evaluating the Effect of Honey as a Natural Remedy for the Management of Sore Throat - Muhammad Hamza,; Zahin Anjum,; Rameesha Aftab,; Ghulam Fatima,; Memoona Fatima,; Ayesha Umar Chaudhary,; Aisha Infall,; Sadaf Naveed, (Indus Journal of Bioscience Research, 2024)
Background: Sore throat is the most common condition in patients suffering with tonsillitis, allergies, sinus drainage as well as viral or bacterial infections. Conventional treatments of sore throat include antibiotics, lozenges and pain relievers but now-a-days, there is an increasing trend to use natural remedies, because of the side effects of antibiotics such as antibiotic resistance. This systematic review examines the effectiveness of honey as a natural therapy for the management of sore throat. Objective: The main objective of the study was to systematically review the supporting evidence regarding the use, effectiveness and potential mechanism of honey as natural remedy for managing the sore throat. Methods: A systematic literature review was conducted from databases like, Google Scholar, PubMed, as well as Science Direct, to collect relevant studies regarding the use of honey as a remedy for the management of sore throat. The search was conducted using keywords like "sore throat," "honey," "pharyngitis," "anti-inflammatory," and "antimicrobial." Studies including comparative effectiveness with other natural remedies were also considered. Results: Studies demonstrates that honey exert a significant impact to relieve symptoms of sore throat such as soothing the tissue irritation as well as pain reduction. Honey has antimicrobial and anti-inflammatory properties that ultimately contributes to its effectiveness in managing the viral and bacterial infections. Many studies also highlight the role of honey in coating the throat as well as promoting the hydration. Conclusion: Honey is an easily available product in the household, having anti-microbial, anti-inflammatory as well as antioxidant properties. Studies shows that honey is a best remedy to reduce the fever, pain, as well as oropharyngeal congestions. Moreover, there is no resistance of side effects on the intake of honey, thereby considered a safe treatment method. However, the consistency and quality of honey, dosage variations, as well as limited large-scale clinical trials highlights that there is a still need to conduct various researches